Participatory Approaches for Varietal Improvement, Itas Significances and Challenges in Ethiopia and Some Other Countries: A Review (Global Journal of Science Frontier Research, 2017)
Participatory approaches such as participatory plant breeding (PPB) and participatory varietal selection (PVS) have become a motivating force for agricultural research and rural development. These approaches have been developed over the past decades as an alternative to centralised breeding methods designed to better incorporate the perspective of end users into the varietal development process to efficiently address the desires of the farmers for increasing food security and improving livelihoods of farmers, especially in resource poor areas. In search of this concept, this review paper discusses the concepts, advantages, experiences, impact and challenges in these participatory approaches stressing the existing evidence of success by various authorities from different countries. In PPB, farmers are actively involved in the breeding process, from setting goals to selecting variable, early generation material. In PVS, farmers are given a wide range of new cultivars to test for themselves in their own fields.
Keywords: participatory; PVS; PPB; farmers; improved varieties